ANALISIS CEMARAN LOGAM BERAT KADMIUM (Cd) DALAM JAMU PEGAL LINU DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Gabriel Lauranita Geovanny Devi; Maria Mita Susanti (Journal Clinical Pharmacy and Pharmaceutical Science, 2022)
Pegal linu traditional medicine is one of tradisional medicine that are in great demand by the community, such as in the district of Mranggen, Demak, as much as 66,50% of the people consume pegal linu traditional medicine. One of the security aspects that need to be considered in traditional medicine is the presence of heavy metal contamination. The research aims to determine the levels of Cd heavy metals in pegal linu traditional medicine with capsule dosage forms that are based on the district of Mranggen, Demak are in accordance with the regulation of BPOM RI in 2014 regrading heavy metal contamination in traditional medicines, ≤ 0,3 mg/kg. This research use explorative experimental, including : sampling, sample preparation used wet closed destruction method with HNO3 and H2SO4 (3:1)  of the destruction solution in the Kjeldhal flask, qualitative analysis of Cd with color test and Cd quantitative analysis using Atomic Absorption Spectroscopy (AAS). The results of the quantitative analysis in this study did not show the metal content of Cd, this was due the small Cd content in the sample. Quantitative analysis shows that the Cd level in 12 sampels of pegal linu traditional medicine circulating in the distric of Mranggen, Demak exceeded the threshold of heavy metal contamination determined by BPOM RI in 2014 with the highest average levels of 18,86 mg/kg and the lower average levels of 7,38 mg/kg.